What is the Role of Religious Coping Activities on the Relationship between Religiosity and Life Satisfaction? A Study On Retirees - (:unkn) unknown (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2016)
This article examines the relationship between religiosity, religious coping and life satisfaction among retired people. Socio-demographic variables (gender, marital status etc.) are also examined in the study. Correlational survey method and questionnaire technique are used. The sample covers 200 retirees whose age range is from 41 to 99. Religiosity Scale, Religious Coping Scale, and The Satisfaction with Life Scale are applied. The findings indicate that retired people had the highest scores in two subscales of religious coping: Heading towards God and Benevolent Religious Reappraisal. According to findings they also had high scores in life satisfaction. Gender was only significant variable on Religious Pleading and Spiritual Discontentment subscales. There was no significant relationship between gender and life satisfaction. According to regression analysis religiosity has positive effect on both positive religious coping and life satisfaction. Findings also indicated that positive religious coping is partial mediating factor on the relationship between religiosity and life satisfaction. Implications of these results and suggestions for future research are discussed.
Keywords: Religiosity; Religious Coping; Life Satisfaction; Spirituality; Mediating Factor; Benevolent Religious Reappraisal; Religious Pleading; Spiritual Discontentment; MEDIATOR; AGE